Tunable room-temperature ferromagnetism in Co-doped two-dimensional van der Waals ZnO - Rui Chen; Fuchuan Luo; Yuzi Liu; Yu Song; Yu Dong; Shan Wu; Jinhua Cao; Fuyi Yang; Alpha N’Diaye; Padraic Shafer; Yin Liu; Shuai Lou; et al. (Nature Communications, 2021)
Van der Waals magnetic materials (vdWs) have allowed for the exploration of the two dimensional limit of magnetism, however, most vdWs are only magnetic at low temperature. Herein, the authors overcome this limitation, observing room temperature magnetic ordering in Cobalt doped graphene-like Zinc-Oxide.